2014
DOI: 10.3382/ps.2013-03540
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the feed intake and growth performance of broiler chickens challenged by bacteria

Abstract: The aim of this meta-analysis was to determine the effect of a bacterial immune challenge (Clostridium spp., Escherichia coli, and Salmonella spp.) on the ADFI, ADG, and nutrient partitioning (maintenance requirements and feed efficiency) of broiler chickens. The database used for the meta-analysis included 65 articles that were published between 1997 and 2012 concerning a total of 86,300 broilers and containing information on the feed intake, protein intake, methionine intake, and weight gain of broilers that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 87 publications
6
30
0
1
Order By: Relevance
“…In the present study, the control infected group with E. coli showed varied clinical signs according to their age, an organ involved, and concurrent disease conditions. Results of Clinical signs in the E. coli infected groups (even in the treated one) similar to results of Remus et al [12] who recorded severe liver damage occurs in cases of E. coli infection. However, dietary supplementation of agrimos ® decreased the clinical signs and PM lesions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, the control infected group with E. coli showed varied clinical signs according to their age, an organ involved, and concurrent disease conditions. Results of Clinical signs in the E. coli infected groups (even in the treated one) similar to results of Remus et al [12] who recorded severe liver damage occurs in cases of E. coli infection. However, dietary supplementation of agrimos ® decreased the clinical signs and PM lesions.…”
Section: Discussionsupporting
confidence: 87%
“…[33]. Remus et al[12] reported E. coli caused severe liver and epithelial damage. However, agrimos ® supplementation to broilers revealed no pathological changes.…”
mentioning
confidence: 99%
“…The partition between these two effects was calculated using (1) the adjusted ΔG mean (obtained from previously fitted equations) and (2) the ΔFI mean observed in the database. A similar interpretation has been used in previous studies on health challenges (Pastorelli et al, 2012;Remus et al, 2014).…”
Section: Methodsmentioning
confidence: 84%
“…Os resultados médios obtidos foram ajustados por covariância para o peso vivo dos animais (peso médio nas variáveis de desempenho e peso ao abate nas variáveis de carcaça). Os interceptos das equações que estimavam o consumo diário de lisina total (expresso em g/dia) em função do ganho diário de peso (expresso em g/dia) dos animais foram utilizados empiricamente como indicadores da exigência de mantença dos animais, uma vez que expressam o nível de consumo do nutriente no qual o ganho de peso é nulo (REMUS et al, 2014). Todas as análises foram realizadas através do programa MINITAB 15.…”
Section: Methodsunclassified